Class and Culture: A Study of Social Dynamism - Thapa, Dharma (Tribhuvan University Journal, 2016)
The author of this article makes an attempt to explore how culture emerged and became a tool of perpetuating or resisting exploitative social order. An attempt has been made to show how, like capital, culture is produced by the working class but the exploiting class appropriates it and turns it against the interests of the producer. It also tries to show that, as a dynamic component of class struggle, the dominance of the capitalist culture can be challenged, resisted, and at times replaced by the culture of the dominated class.